WORKER’S MENTAL HEALTH: STRESS LEVEL AND MEANINGS OF MENTAL HEALTH BY WORKERS IN A CHILDREN’S INSTITUTIONAL CARE - Eugênia Fernandes do Rêgo , Magna (Health and Society, 2022)
With increasing globalization and its consequences, mental health at work has been gaining more and more space in socio-political discussions and proposals, as it consists of taking a different look at the worker and the forms of work, aiming the biopsychosocial well-being of the subject in the format of health promotion and prevention. The space of Special Social Protection of High Complexity within the Social Assistance policy deals with high-risk vulnerability demands, with subjects coming from different forms of social segregation, in this emphasis, workers in this area are directly exposed to intense forms of psychic suffering. , including stress. With that, the objective of the present work is to verify the level of stress and meanings of the mental health in the workers of an institutional shelter for children. A field research was carried out in the referred institution with the workers where the Inventory of Stress Symptoms for Adults of Lipp (ISSL) and a qualiquantitative questionnaire were applied to obtain answers about the concepts of mental health that they have and strategies for obtaining/maintaining of it, as well as the mental health situation of these subjects. It was found that most respondents were classified with one of the three phases of stress and of these, most are in the second phase, which is Resistance or Fight, on the perception of mental health most pointed to a similar concept to the concept real, as well as self-assessed with very good mental health. With this, it is worth deepening preventive care with the mental health of Social Assistance workers, especially with regard to stress.